Attenuation of Diabetic Nephropathy by Carvacrol through Anti-oxidative Effects in Alloxan-Induced Diabetic Rats - Hamid Reza Jamshidi; Zahra Zeinabady; Ehsan Zamani; Mohammad Shokrzadeh; Fatemeh Shaki* (Iranian Society of Pharmacognosy, 2018)
Background and Objectives: Diabetes, a common metabolic disorder, is prevalent in many countries. Nephropathy is a main debate's side effect. Role of oxidative stress is well known in induction of diabetic nephropathy while carvacrol is a potent anti-oxidant that might attenuate oxidative stress. The aim of this study was to explore the effect of carvacrol in decreasing nephropathy-induced oxidative damage in diabetic rats. Methods: Thirty five Wistar rats (200-250 g) were divided to 7 groups. The rats received alloxan (i.p., 200 mg/kg) for induction of diabetes. After one week, fasting blood sugar (FBS) was assessed and the rats with FBS>250 mg/dL were considered as diabetic. Three weeks after alloxan injection, the blood urea (BUN) and creatinine (Cr) were determined for confirmation of inducing nephropathy. Then, the animals were treated with carvacrol for one week. Finally, they were anesthetized and blood was collected from animal's heart for calculation of BUN and Cr. Furthermore, the kidneys were for oxidative stress markers such as glutathione capacity, protein carbonyl, lipid peroxidation and catalase activity. Results: Our results showed that glutathione level and catalase activity significantly increased after treatment with carvacrol. Same results were found in rats that received vitamin E. Also, lipid peroxidation, protein carbonyl content, BUN and Cr levels significantly decreased after treatment with carvacrol in comparison with diabetic rats. Conclusion: Our results showed that carvacrol improved nephropathy-induced oxidative damage similar to vitamin E. Therefore, it may be suggested that carvacrol can be suggested as a useful supplement in decreasing diabetic complaints along with anti-diabetic drugs.